Reducing Igf-1r levels leads to paradoxical and sexually dimorphic effects in HD mice. - Silvia Corrochano; Maurizio Renna; Georgina Osborne; Sarah Carter; Michelle Stewart; Joel May; Gillian P Bates; Steve D M Brown; David C Rubinsztein; Abraham Acevedo-Arozena (PLoS ONE)
Many of the neurodegenerative diseases that afflict people in later life are associated with the formation of protein aggregates. These so-called "proteinopathies" include Alzheimer's disease (AD) and Huntington's disease (HD). The insulin/insulin-like growth factor signalling (IIS) pathway has been proposed to modulate such diseases in model organisms, as well as the general ageing process. In this pathway, insulin-like growth factor binds to insulin-like growth factor receptors, such as the insulin-like growth factor 1 receptor (IGF-1R). Heterozygous deletion of Igf-1r has been shown to lead to increased lifespan in mice. Reducing the activity of this pathway had benefits in a HD C. elegans model, and some of these may be attributed to the expected inhibition of mTOR activity resulting in an increase in autophagy, which would enhance mutant huntingtin clearance. Thus, we tested if heterozygous deletion of Igf-1r would lead to benefits in HD related phenotypes in the mouse. Surprisingly, reducing Igf-1r levels led to some beneficial effects in HD females, but also led to some detrimental effects in HD males. Interestingly, Igf-1r deficiency had no discernible effects on downstream mTOR signalling in HD mice. These results do not support a broad beneficial effect of diminishing the IIS pathway in HD pathology in a mammalian system.